Comparison of the growth of green algae, Nephroselmis sp. at different media - Agana, Julie Ann Ecto
Green algae play a significant role in the maintenance of the hatchery of economically important crustaceans where a continuous supply of algae is needed to feed the larvae. Moreover, microalgae have the potential to be used to produce chemically complex molecules, which are difficult to synthesize. Thus, the present was conducted to compare the growth of the green algae, Nephroselmis sp. using three diffeent media. Specifically, the study aims (1) to compare the effect of diffeent media on the growth of Nephroselmis sp. and (2) to determine which medium is the most suitable for growth of Nephroselmis sp. The result of the study showed that there was no significant difference in the growth of the green algae Nephroselmis sp. at three different media. The results showed that quantities of chemical composition of the different media are already sufficient for the growth of Nephroselmis sp.